Abraham in the Book of Jubilees : the rewriting of Genesis 11:26-25:10 in the Book of Jubilees 11:14-23:8 - Ruiten, J. van (Jacques) (Leiden ; Boston : Brill, 2012)
In Abraham in the Book of Jubilees Jacques van Ruiten offers a systematic analysis of one of the most important and extensive Second Temple Jewish treatments of the figure of Abraham (Jub. 11:14-23:8).
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 630
Keywords: Book of Jubilees, XI, 14-23:8 -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Abraham -- (Biblical patriarch); Abraham, -- Biblical patriarch; RELIGION -- Biblical Studies -- Bible Study Guides; Electronic books